2018
DOI: 10.1101/303594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and biochemical characterization of a novel PP2C-like Ser/Thr phosphatase inE. coli

Abstract: 15In bacteria, signaling phosphorylation is thought to occur primarily on His and Asp 16 residues. However, phosphoproteomic surveys in phylogenetically diverse bacteria over 17 the past decade have identified numerous proteins that are phosphorylated on Ser and/or 18 Thr residues. Consistently, genes encoding Ser/Thr kinases are present in many bacterial 19 genomes such as E. coli, which encodes at least three Ser/Thr kinases. Since Ser/Thr 20 phosphorylation is a stable modification, a dedicated phosphatase… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Our laboratory previously identified a novel PP2C‐like phosphatase in the E. coli genome encoded by the pphC ( yegK ) gene [13]. Often, phosphatases of this class are found proximal to eukaryotic‐like Ser/Thr kinases (eSTKs) [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory previously identified a novel PP2C‐like phosphatase in the E. coli genome encoded by the pphC ( yegK ) gene [13]. Often, phosphatases of this class are found proximal to eukaryotic‐like Ser/Thr kinases (eSTKs) [7].…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that a His 6 ‐tagged version of YegI is capable of autophosphorylation [13] despite the absence of three of the ten absolutely conserved residues (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%